2019
DOI: 10.1063/1.5123790
|View full text |Cite
|
Sign up to set email alerts
|

Excess electron solvation in ammonia clusters

Abstract: We performed a combination of quantum chemical calculations and molecular dynamics simulations to assess the stability of various size NH3n− ammonia cluster anions up to n = 32 monomers. In the n = 3–8 size range, cluster anions are optimized and the vertical detachment energy of the excess electron (VDE) from increasing size clusters is computed using various level methods including density functional theory, MP2, and coupled-cluster singles doubles with perturbative triples. These clusters bind the electrons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(46 citation statements)
references
References 57 publications
3
43
0
Order By: Relevance
“… 24 Most recently, we also performed ab initio and DFT calculations on ammonia cluster anions, extending the investigated systems up to 32 monomers. 23 We found that long extended chains of ammonia cluster anions localize less than 1% of the excess electron density in the frontier orbitals of the nitrogen atoms, a minor effect that largely supports Sommerfeld’s view. 24 Although this argument seems to be valid for chains of dipole bound anions, one has to realize that physical properties observed for finite size systems are not necessarily transferable to the bulk.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“… 24 Most recently, we also performed ab initio and DFT calculations on ammonia cluster anions, extending the investigated systems up to 32 monomers. 23 We found that long extended chains of ammonia cluster anions localize less than 1% of the excess electron density in the frontier orbitals of the nitrogen atoms, a minor effect that largely supports Sommerfeld’s view. 24 Although this argument seems to be valid for chains of dipole bound anions, one has to realize that physical properties observed for finite size systems are not necessarily transferable to the bulk.…”
Section: Introductionsupporting
confidence: 71%
“…We performed ab initio molecular dynamics simulations to model excess electron solvation in finite size ammonia clusters. Since the applied methods are similar to those employed in a previous work, 23 we outline the simulation techniques only briefly here, but provide more discussion on a few specific key details.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations